Case Report: ALK-Positive Histiocytosis With KIF5B-ALK Fusion in Cerebrum-Disseminated Lesions in a Child - Guo, Yi; Qu, Hai-bo; Ning, Gang; Jia, Feng-lin; Liu, Hong; Ma, Xin-mao; Liao, Yi (Frontiers in Oncology, 2022)
Background: Anaplastic lymphoma kinase (ALK)-positive histiocytosis is a rare type of histiocytosis that could affect multiple systems in children and adults. 10 cases of ALK-positive histiocytosis invading the central nervous system (CNS) have been reported. Herein, we report a case of ALK-positive histiocytosis invading the central nervous system and lungs and the details of follow-up of tumor dynamic changes during treatment. Case presentation: An 18-month-old boy was underweight and had slow growth of almost 3 months duration. The child could not stand and walk independently, and his language and intelligence development occurred later than those of his peers. Cranial magnatic resonance imaging revealed a giant suprasellar lesion with isosignal, measuring approximately 5.1× 3.6× 4.0 cm on T1-weighted imaging, with an obvious mass effect. Nodular, slightly low-signal shadows were also observed in the left temporal pole and left hippocampus, measuring approximately 1.0 cm × 0.7 cm× 0.5 cm and 0.9 cm× 0.8 cm × 0.5 cm on T1-weighted, respectively. The child underwent partial resection of the suprasellar lesion, and a diagnosis of ALK-positive histiocytosis was made histologically. Subsequently, the patient received chemotherapy (CHOP regimen) and anti-ALK therapy (crizotinib). The lesions were gradually shrinking without dissemination and the changes of intracranial and lung lesions were monitored with imaging during therapy. Unfortunately, the child died 8 months after the first surgery because of worsening intracranial infection. Conclusion: ALK-positive histiocytosis may involve the central nervous system and disseminate intracranially. ALK-positive histiocytosis should be considered for the differential diagnosis of suprasellar lesions.